Refining trace metal temperature proxies in cold-water scleractinian and stylasterid corals - Stewart, Joseph A.; Robinson, Laura F.; Day, Russell D.; Strawson, Ivo; Burke, Andrea; Rae, James W.B.; Spooner, Peter T.; Samperiz, Ana; Etnoyer, Peter J.; Williams, Branwen; Paytan, Adina; Leng, Melanie J.; et al. (Earth and Planetary Science Letters, 2020)
Funding was provided by an Antarctic Bursary awarded to J.A.S., ERC and NERC grants awarded to L.F.R. (278705, NE/S001743/1, NE/R005117/1) and L.F.R. and J.W.B.R. (NE/N003861/1), and a NERC Stable isotope Grant. The Li/Mg, Sr/Ca and oxygen isotopic (δ18O) compositions of many marine biogenic carbonates are sensitive to seawater temperature. Corals, as cosmopolitan marine taxa with carbonate skeletons that can be precisely dated, represent ideal hosts for these geochemical proxies. However, efforts to calibrate and refine temperature proxies in cold-water corals (<20◦C) remain limited. Here we present skeletal Li/Mg, Sr/Ca, δ18O and carbon isotope (δ13C) data from live-collected specimens of aragonitic scleractinian corals (Balanophyllia, Caryophyllia, Desmophyllum, Enallopsammia, Flabellum, Lophelia, and Vaughanella), both aragonitic and high-Mg calcitic stylasterid genera (Stylaster and Errina), and shallow-water high-Mg calcite crustose coralline algae (Lithophyllum, Hydrolithon, and Neogoniolithon). We interpret these data in conjunction with results from previously explored taxa including aragonitic zooxanthellate scleractinia and foraminifera, and high-Mg calcite octocorals. We show that Li/Mg ratios covary most strongly with seawater temperature, both for aragonitic and high-Mg calcitic taxa, making for reliable and universal seawater temperature proxies. Combining all of our biogenic aragonitic Li/Mg data with previous calibration efforts we report a refined relationship to temperature: Li/MgAll Aragonite=5.42 exp(−0.050 ×T(◦C))(R2=0.97). This calibration now permits paleo-temperature reconstruction to better than ±3.4◦C (95% prediction intervals) across biogenic aragonites, regardless of taxon, from 0 to 30◦C. For taxa in this study, aragonitic stylasterid Li/Mg offers the most robust temperature proxy (Li/MgStylasterid(Arag)=5.64 exp(−0.046 ×T(◦C))(R2=0.95)) with a reproducibility of ±2.3◦C. For the first time, we show that high-Mg calcites have a similar exponential relationship with temperature, ...